Hepatic IGF2/H19 Epigenetic Alteration Induced Glucose Intolerance in Gestational Diabetes Mellitus Offspring via FoxO1 Mediation - Jiang, Ying; Zhu, Hong; Chen, Zi; Yu, Yi-Chen; Guo, Xiao-Han; Chen, Yuan; Yang, Meng-Meng; Chen, Bang-Wu; Sagnelli, Matthew; Xu, Dong; Zhao, Bai-Hui; Luo, Qiong (Frontiers in Endocrinology, 2022)
Objective The offspring of women with gestational diabetes mellitus (GDM) have a high predisposition to developing type 2 diabetes during childhood and adulthood. The aim of the study was to evaluate how GDM exposure in the second half of pregnancy contributes to hepatic glucose intolerance through a mouse model. Methods By creating a GDM mouse model, we tested glucose and insulin tolerance of offspring by intraperitoneal glucose tolerance test (IPGTT), insulin tolerance test (ITT), and pyruvate tolerance test (PTT). In addition, we checked the expression of genes IGF2/H19, FoxO1, and DNMTs in the mouse liver by RT-qPCR. Pyrosequencing was used to detect the methylation status on IGF2/H19 differentially methylated regions (DMRs). In vitro insulin stimulation experiments were performed to evaluate the effect of different insulin concentrations on HepG2 cells. Moreover, we detect the interaction between FoxO1 and DNMT3A by chromatin immunoprecipitation–quantitative PCR (Chip-qPCR) and knock-down experiments on HepG2 cells. Results We found that the first generation of GDM offspring (GDM-F1) exhibited impaired glucose tolerance (IGT) and insulin resistance, with males being disproportionately affected. In addition, the expression of imprinted genes IGF2 and H19 was downregulated in the livers of male mice via hypermethylation of IGF2-DMR0 and IGF2-DMR1. Furthermore, increased expression of transcriptional factor FoxO1 was confirmed to regulate DNMT3A expression, which contributed to abnormal methylation of IGF2/H19 DMRs. Notably, different insulin treatments on HepG2 demonstrated those genetic alterations, suggesting that they might be induced by intrauterine hyperinsulinemia. Conclusion Our results demonstrated that the intrauterine hyperinsulinemia environment has increased hepatic FoxO1 levels and subsequently increased expression of DNMT3A and epigenetic alterations on IGF2/H19 DMRs. These findings provide potential molecular mechanisms responsible for glucose intolerance and insulin resistance in the first male generation of GDM mice.